2019
DOI: 10.1002/pssb.201900285
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phase Distribution and Ferroelectricity in Ultrathin HfO2–ZrO2 Bilayers

Abstract: (Hf,Zr)O2 ultrathin films are used as ferroelectric layers in emerging digital logic and nonvolatile memory devices. The ferroelectric properties of (Hf,Zr)O2 can be improved by interface engineering, such as the formation of nanolaminates with distinct HfO2 and ZrO2 layers. Herein, the ferroelectric performance of HfO2–ZrO2 ultrathin bilayer devices is shown to depend on the stacking order of HfO2 and ZrO2, which affects the quantity of the noncentrosymmetric orthorhombic Pca21 crystal phase. By combining X‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Pca2 1 phase found in ultrathin films of hafnia‐based dielectrics are nonexistent in the bulk form to be used as reference foil for acquiring model or a calibration spectra. The theoretical spectra are simulated from the static average atomic positions and the thermal disorder in these structure models are included using the model proposed by McBriarty et al [ 34 ] A linear relation ( σ D 2 = a * R eff + b ) between the disorder coefficients σ D 2 and effective path length R eff was used to estimate the crystal phase distribution in HfO 2 –ZrO 2 nanolaminates. The constants a and b were appraised by analyzing a ZrO 2 ‐powdered sample and a ZrO 2 MIM stack and were used subsequently in the LCF analysis of the three HZO samples of interest here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pca2 1 phase found in ultrathin films of hafnia‐based dielectrics are nonexistent in the bulk form to be used as reference foil for acquiring model or a calibration spectra. The theoretical spectra are simulated from the static average atomic positions and the thermal disorder in these structure models are included using the model proposed by McBriarty et al [ 34 ] A linear relation ( σ D 2 = a * R eff + b ) between the disorder coefficients σ D 2 and effective path length R eff was used to estimate the crystal phase distribution in HfO 2 –ZrO 2 nanolaminates. The constants a and b were appraised by analyzing a ZrO 2 ‐powdered sample and a ZrO 2 MIM stack and were used subsequently in the LCF analysis of the three HZO samples of interest here.…”
Section: Resultsmentioning
confidence: 99%
“…From the results of Table 2, it is shown that phase percentages estimates are within <20%, and there is no bias in estimating particular crystal phase fraction in these calculations. Two key factors that play a major role in LCF results of the data are binding energy offset and linear parametrization of disorder as explained by McBriarty et al [ 34 ] Simple disorder parametrization may lead to minor distortions in the amplitude of the LCF basis spectra and thereby differences in the fit compared with those obtained from true phase‐pure standard samples. However, the phase‐pure standards of Pca2 1 do not exist in the bulk form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of ferroelectric properties on HfO 2 /ZrO 2 nanolaminate samples experimentally observed from ref [21][22][23][33][34][35][36]…”
mentioning
confidence: 99%